2001
DOI: 10.1074/jbc.m008356200
|View full text |Cite
|
Sign up to set email alerts
|

The Ectodermal Dysplasia Receptor Activates the Nuclear Factor-κB, JNK, and Cell Death Pathways and Binds to Ectodysplasin A

Abstract: The ectodermal dysplasia receptor (EDAR) is a recently isolated member of the tumor necrosis factor receptor family that has been shown to play a key role in the process of ectodermal differentiation. We present evidence that EDAR is capable of activating the nuclear factor-B, JNK, and caspase-independent cell death pathways and that these activities are impaired in mutants lacking its death domain or those associated with anhidrotic ectodermal dysplasia and the downless phenotype. Although EDAR possesses a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
1
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 46 publications
4
130
1
4
Order By: Relevance
“…The emerging model has the EDA ligand, a transmembrane protein, binding its receptor, EDAR (15,16,50), and signaling to the target cell through activation of the NF-B system of transcriptional regulation (50,51). During tooth development in mouse, signaling between EDA and its receptor, EDAR, is required to establish and maintain enamel knot morphology and function (16,52).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging model has the EDA ligand, a transmembrane protein, binding its receptor, EDAR (15,16,50), and signaling to the target cell through activation of the NF-B system of transcriptional regulation (50,51). During tooth development in mouse, signaling between EDA and its receptor, EDAR, is required to establish and maintain enamel knot morphology and function (16,52).…”
Section: Discussionmentioning
confidence: 99%
“…44,45 It encodes a death-domain containing member of the TNF-R family, EDAR, and is a specific receptor for ectodysplasin. 46,47 Its expression is restricted to placodes, thickenings of epithelia where epidermal appendages begin to form. 48,49 The third locus whose disruption leads to EDA has been identified only recently in crinkled mice and subsequently found mutated in a human family.…”
Section: Incontinentia Pigmentimentioning
confidence: 99%
“…Additional biochemical studies have confirmed that ectodysplasin/EDAR interaction indeed results in NF-kB activation. 31,47,52 Therefore, mutations in three genes that encode members of a signaling cascade that leads to NF-kB activation result in anhidrotic ectodermal dysplasia. Although the details of the ectodysplasin/EDAR signaling pathway are not fully characterized, it is clear from analyzing the mouse models of EDA pathology that this pathway is involved very early during development of hair follicle morphogenesis, 44 assigning a previously unrecognized role for NF-kB in this process.…”
Section: Incontinentia Pigmentimentioning
confidence: 99%
“…Eda signaling and Troy are believed to be mediated by NF-B (Kojima et al, 2000;Yan et al, 2000;Kumar et al, 2001). Indeed mutations in certain components of the NF-B pathway have molar cusp abnormalities (Hu et al, 1999b;Li et al, 1999;Takeda et al, 1999;Makris et al, 2000;Zonana et al, 2000;Dö ffinger et al, 2001; Ohazama et al, manuscript submitted for publication).…”
Section: Tooth Phenotype In Traf6 Mutant Micementioning
confidence: 99%